From Text to Battle: Fame and rumor in the Civil Wars (49 a 45 b.c e 68-69 A.D.) (Mare Nostrum, 2015)
This article aims at studying the rumors that were evidenced in Latin literature during the civil wars between Caesar and Pompey and the Year of the Four Emperors. For this study, I’ve selected two different words, fama and rumor, and I hope to discuss and explore all possible connections between them and the political and social relations in the war environment through a theoretical approach that prioritizes a new vision of the rumors inside classical literature. I believe that the rumors, though they could represent a controversial perspective on the available sources, for they are usually understood only as a literary device, they could be a key theme to bring to light aspects that will help us understand the interaction of the agents involved in Civil Wars.